Sustainable Research and Technological Development on Bio-Energy - Abdeen Mustafa Omer (Candela Edutech Indonesia, 2025)
This paper discusses a comprehensive review of biomass energy sources, environment and sustainable development. This includes the biomass energy technologies, energy efficiency systems, energy conservation scenarios, energy savings and other measures necessary to reduce climate change. Energy use reductions can be achieved by minimising the energy demand, by rational energy use, and by recovering heat. The increased availability of reliable and efficient energy services stimulates the use of more green energies. The adoption of green or sustainable approaches to the way in which society is run is seen as an important strategy in finding a solution to the energy problem. The key factors to reducing and controlling CO2 emissions to the atmospheric sink, which is the major contributor to global warming, are the use of alternative approaches to energy generation and the exploration of how these alternatives are used today and may be used in the future as green energy sources.